Ionization-driven intrinsic absorption line variability of BAL quasars in the Stripe 82 region. Issue 2 (3rd April 2019) - Vivek, M
Abstract: We investigate the connection between the intrinsic C iv absorption line variability and the continuum flux changes of broad absorption line (BAL) quasars using a sample of 78 sources in the Stripe 82 region. The absorption trough variability parameters are measured using the archival multi-epoch spectroscopic data from the Sloan Digital Sky Survey (SDSS), and the continuum flux variability parameters are estimated from the photometric light curves obtained by the SDSS and the Catalina Real-Time Survey surveys. We find evidence for weak correlations (ρs ∼ 0.3) between the intrinsic C iv absorption line variability and the quasar continuum variability for the final sample of 78 BAL quasars. The correlation strengths improve (ρs ∼ 0.5) for the 'high-signal-to-noise ratio (SNR)' sample sources that have higher spectral SNR. Using two subsets of the high-SNR sample differing on the absorption trough depth, we find that the shallow-trough subset shows an even stronger correlation (ρs ∼ 0.6), whereas the deep-trough subset does not show any correlation between the absorption line variability and the continuum variability. These results point to the important role of saturation effects in the correlation between the absorption line variability and the continuum variability of BAL quasars. Considering other effects that can also smear the correlation, we conclude that the actual correlation between the absorption line and continuum variability is even stronger.